Do Financial Institutions Practice Less Tax Avoidance than Other Companies? - Santos, Rogiene Batista dos; Rezende, Amaury José; Prado , Fernando Pigeard de Almeida (Revista de Contabilidade da UFBA, 2024)
This study investigates whether financial institutions engage in greater tax aggressiveness compared to other sectors, addressing a significant gap in the literature by exploring sector-specific tax behaviors and their broader implications. The hypothesis suggests that financial institutions exhibit lower GAAP ETRs (Generally Accepted Accounting Principles Effective Tax Rates) and CASH ETRs (Cash Effective Tax Rates) than non-financial companies. Using a robust dataset of 131,204 firm-year observations from publicly traded U.S. companies between 2000 and 2022, sourced from the Compustat database, the study employs advanced regression methods, including quantile regression, to analyze these dynamics. While traditional regression results indicate no significant difference in tax avoidance between financial and non-financial firms, quantile regression uncovers critical nuances. At higher levels of tax avoidance, financial institutions are less likely to engage in aggressive practices. The findings offer significant contributions to public policy by highlighting the role of reputational factors in moderating tax behaviors, providing policymakers with insights for designing regulations that balance tax compliance and competitiveness. For education, this study introduces real-world examples of sector-specific tax strategies, enabling educators to incorporate these findings into accounting and finance curricula to better prepare students for challenges in corporate governance and fiscal policy.